Pulse pressure and pulse wave velocity are related to cognitive decline in the Baltimore Longitudinal Study of Aging - Waldstein, Shari R; Rice, S Carrington; Thayer, Julian F; Najjar, Samer S; Scuteri, Angelo; Zonderman, Alan B (Hypertension (Dallas, Tex. 1979), 2008)
Pulse pressure and pulse wave velocity, markers of arterial stiffness, have been associated with stroke, dementia, and lowered levels of cognitive function. Here we examine longitudinal relations of pulse pressure and pulse wave velocity to multiple domains of cognitive function among nondemented, stroke-free persons. Up to 1749 participants from the Baltimore Longitudinal Study of Aging completed tests of verbal and nonverbal memory, attention, perceptuo-motor speed, confrontation naming, executive functions, and cognitive screening measures, as well as concurrent sphygmomanometric assessment of blood pressure (for derivation of pulse pressure) on 1 to 8 occasions over 14 years. A subset of <or=582 participants also underwent a single baseline assessment of pulse wave velocity and cognitive assessment on 1 to 6 occasions over 11 years. Results of mixed-effects regression models revealed a prospective decline on tests of verbal learning, nonverbal memory, working memory, and a cognitive screening measure among those with increasing levels of pulse pressure (P<0.05). Persons with higher baseline pulse wave velocity also exhibited prospective decline on tests of verbal learning and delayed recall, nonverbal memory, and a cognitive screening measure (P<0.05). Markers of arterial stiffness are associated prospectively with cognitive decline before dementia. Aggressive treatment of risk factors associated with greater arterial stiffness may help preserve cognitive function with individuals' increasing age.